SLAVERY IN MARK TWAIN’S THE ADVENTURES OF HUCKLEBERRY FINN: A SOCIOLOGICAL PERSPECTIVE - Nainggolan, Redelina Fransiska; Rorintulus, Olga A.; Mogea, Tini (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aimed to reveal the Slavery in The Adventures of Huckleberry Finn that is shown by the main character Jim. This study uses qualitative research because the data are in the form of words rather than numbers. The data collected in this research are in the form of two sources: they are the primary data and secondary data. The primary source is the novel itself, and the secondary sources are references such as books, journals and the internet which are relevant to the research. In analyzing data the writer uses a sociological approach. The result of this research shows there is Slavery in Mark Twain’s the Adventures of Huckleberry Finn and discussed in three parts. chattel slavery, the oppressed life of black slaves, impact slavery.